2021
DOI: 10.1007/s10764-021-00200-y
|View full text |Cite
|
Sign up to set email alerts
|

Using Utilitarian Plants for Lemur Conservation

Abstract: Nature and species conservation often conflict with intensive natural resource or land use. Many protected areas are too small for long-term conservation of viable vertebrate populations, especially in Madagascar, and forests are subject to exploitation for a variety of natural resources. Trying to exclude people from the use of these resources has not been successful during economic, natural, or political crises or when human population growth outruns any development effort. People need economic and other ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Some evidence suggests that aggressive shrubby and herbaceous species may outcompete rain forest trees in regenerating areas, especially in heavily degraded locations where non‐forest species may be better adapted to new nutrient and fire regimes (De Wilde et al, 2012; Konersmann et al, 2021; Rasolofoharinoro et al, 1997; Styger et al, 2007). Some of these species are native to Madagascar (e.g., Dicranopteris linearis and Ravenala madagascariensis ), including those representative of fire‐tolerant ericoid thickets found in Malagasy highlands (e.g., Helichrysum bracteiferum and Philippia floribunda ), but invasion by exotic species such as Lantana camara , Rubus moluccanus , and Erica spp.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some evidence suggests that aggressive shrubby and herbaceous species may outcompete rain forest trees in regenerating areas, especially in heavily degraded locations where non‐forest species may be better adapted to new nutrient and fire regimes (De Wilde et al, 2012; Konersmann et al, 2021; Rasolofoharinoro et al, 1997; Styger et al, 2007). Some of these species are native to Madagascar (e.g., Dicranopteris linearis and Ravenala madagascariensis ), including those representative of fire‐tolerant ericoid thickets found in Malagasy highlands (e.g., Helichrysum bracteiferum and Philippia floribunda ), but invasion by exotic species such as Lantana camara , Rubus moluccanus , and Erica spp.…”
Section: Resultsmentioning
confidence: 99%
“…Martinez & Razafindratsima (2014) demonstrate that seed dispersal into regenerating forests by lemurs is possible, but is likely limited during early years of regeneration, farther from forest edges, and in extremely fragmented landscapes, due to a lack of habitat structure (see also Bollen et al, 2004a; Bollen et al, 2004b; de Winter et al, 2018). Incorporating lemur food plants into restoration design, especially those that are relatively fast‐growing early‐successional species, may improve seed dispersal (Konersmann et al 2021; Manjaribe et al, 2013; Peters et al, 2016; Steffens, 2020), but no published comparative studies assessing the effectiveness of this strategy currently exist. Little is known about secondary seed dispersal in Madagascar and its potential role in forest restoration, though Razafindratsima (2017) found that seed predation by rodents was lower in disturbed habitat.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plantations of exotic species planted in the appropriate area can reduce the pressure on the natural forest (Sedjo and Botkin 1997;Gérard et al 2015;Konersmann et al 2021). Studies have also shown that socio-cultural value of timber species increases with the increase of their availability and accessibility (Thomas et al 2009;Brandt et al 2013).…”
Section: Construction Materials Firewood and Othermentioning
confidence: 99%